2015
DOI: 10.1097/iae.0000000000000602
|View full text |Cite
|
Sign up to set email alerts
|

Inner Nuclear Layer Thickness as a Prognostic Factor for Metamorphopsia After Epiretinal Membrane Surgery

Abstract: Inner nuclear layer thickness was found to be a good indicator of metamorphopsia both before and after surgery and a predictor of postoperative metamorphopsia in patients with epiretinal membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
84
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 37 publications
7
84
0
2
Order By: Relevance
“…Okamoto et al 7,10 reported that the preoperative aniseikonia score was significantly correlated with the thicknesses of the retinal ganglion cell (RGC) layer and the inner nuclear layer (INL). In addition, the postoperative aniseikonia scores at 3 months and 6 months were significantly correlated with the INL thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Okamoto et al 7,10 reported that the preoperative aniseikonia score was significantly correlated with the thicknesses of the retinal ganglion cell (RGC) layer and the inner nuclear layer (INL). In addition, the postoperative aniseikonia scores at 3 months and 6 months were significantly correlated with the INL thickness.…”
Section: Discussionmentioning
confidence: 99%
“…MV is thought to be associated with horizontally oriented retinal contraction. Furthermore, MV is thought to be less likely to improve in response to surgery as well as being less likely to occur because of the presence of the optic nerve which may restrict horizontal displacement of the posterior retina and also because of the directionality of the axon of the retinal ganglion cells which course horizontally rather than vertically in the posterior pole [13,21,22]. MH showed improvement in both groups (Moderate group: 0.5°, Good group: 0.37°) at the final observation time point.…”
Section: Discussionmentioning
confidence: 99%
“…Okamoto et al reported that preoperative MCHART score was significantly correlated with the ONL + OPL thickness using SD-OCT images. 9 Ooto et al reported that cone morphologic feature patterns in the foveal photoreceptor layer was associated with metamorphopsia, as assessed using adaptive optics scanning laser ophthalmoscopy images. 22 In this study, circularity is the parameter indicating how the ONL is close to a perfect circle, and area ratio is the parameter indicating whether the contour line of the ONL-B is irregular.…”
Section: Discussionmentioning
confidence: 99%
“…6,8 However, the longitudinal improvement in metamorphosis is not as noteworthy as that of visual acuity. 9 High-resolution spectral domain optical coherence tomography (SD-OCT), which is now the most common retinal imaging device, is widely used to investigate the changes of microstructure in the retina in patients with ERM.…”
Section: Introductionmentioning
confidence: 99%